2011
DOI: 10.1371/journal.pone.0027704
|View full text |Cite
|
Sign up to set email alerts
|

Histological Assessment of PAXgene Tissue Fixation and Stabilization Reagents

Abstract: Within SPIDIA, an EC FP7 project aimed to improve pre analytic procedures, the PAXgene Tissue System (PAXgene), was designed to improve tissue quality for parallel molecular and morphological analysis. Within the SPIDIA project promising results were found in both genomic and proteomic experiments with PAXgene-fixed and paraffin embedded tissue derived biomolecules. But, for this technology to be accepted for use in both clinical and basic research, it is essential that its adequacy for preserving morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 18 publications
9
70
1
2
Order By: Relevance
“…46 In fact, we analyzed two cases of meningioma using genomic DNA extracted from formalin-fixed paraffin-embedded tissue and obtained similar but imprecise results of copynumber alterations (data not shown), mostly because of DNA fragmentation by formalin fixation. [47][48][49] For an appropriate clinical sequencing system, concomitance of conserved histology and high-quality nucleotide extraction must be achieved, therefore an alternative sample preparation method, other than snap-frozen or formalin fixation, such as the PAXgene Tissue System, would be considered.…”
Section: Modern Pathology (2016) 29 708-716mentioning
confidence: 74%
“…46 In fact, we analyzed two cases of meningioma using genomic DNA extracted from formalin-fixed paraffin-embedded tissue and obtained similar but imprecise results of copynumber alterations (data not shown), mostly because of DNA fragmentation by formalin fixation. [47][48][49] For an appropriate clinical sequencing system, concomitance of conserved histology and high-quality nucleotide extraction must be achieved, therefore an alternative sample preparation method, other than snap-frozen or formalin fixation, such as the PAXgene Tissue System, would be considered.…”
Section: Modern Pathology (2016) 29 708-716mentioning
confidence: 74%
“…An alternative to FFPE and fresh frozen preservation is the noncrosslinking PAXgene Tissue System (PreAnalytiX, Hombrechtikon, Switzerland), which has proven to be efficient for preservation of the morphology and allows high-quality extraction of proteins, RNA, and DNA from the fixed tissues [10][11][12][13] The focus on high-quality molecules has increased as the search for new biomarkers has intensified, especially in cancer research. It is now well accepted that the required molecular alterations for neoplastic initiation and progression can, in addition to genetic changes, be acquired through epigenetic mechanisms [14].…”
Section: Introductionmentioning
confidence: 99%
“…In proteomic and genomic assays, proteins and nucleic acids derived from PAXgene-fixed, paraffin-embedded (PFPE) tissues react as those derived from fast frozen tissues. [7][8][9][10] Recently, Cadoret et al 11 showed that DNA isolated from PAXgene-fixed tissue of Atlantic salmon gills could be used to detect Neoparamoeba perurans DNA by polymerase chain reaction (PCR). Also, conventional histological staining and immunohistochemistry (IHC) could be performed on PAXgene-fixed tissue to visualize the amoeboid parasite in salmon gills.…”
Section: Introductionmentioning
confidence: 99%